A Disability Rights Approach to a Constitutional Right to Housing. (21st April 2023) - Sperrin, Áine
Abstract : This article discusses the potential value of a Constitutional Right to Housing in Ireland to the realisation of independent living for disabled people. Article 19 of the United Nations Convention on the Rights of Persons with Disabilities promotes the right of choice over where and with whom to live, the right to access supports to realise your choices and to participate equally in society. Ireland's historic system of institutionalising disabled people is being slowly dismantled, but equally challenging is the lack of available, accessible, and adequate housing in the community. This article outlines how the live issues of defective construction materials, inaccessibility of housing, the invisibility of disabled people's homelessness, and ongoing institutionalisation are preventing full Article 19 UN CRPD realisation. It will suggest how embedding housing as a Constitutional right will contribute to alleviating these rights violations.